2020
DOI: 10.1007/s11136-020-02496-4
|View full text |Cite
|
Sign up to set email alerts
|

Does the EQ-5D-5L benefit from extension with a cognitive domain: Testing a multi-criteria psychometric strategy in trauma patients

Abstract: Purpose This study investigated the psychometric yield of extension of the EQ-5D-5L with a cognitive domain (EQ-5D+C) in a mixed cohort of trauma patients with repeated data. Methods A stratified sample of patients that presented at the emergency department filled out a follow-up survey 6 and 12 months after trauma. The surveys included the EQ-5D-5L+C, EQ-VAS, and the impact of events scale-revised (IES-R), a validated post-traumatic stress disorder (PTSD) self-assessment scale. Generally, results of the EQ-5D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In addition, a frequently used item on cognitive problems in EQ-5D-5L format was included in the survey, informing on problems with memory/understanding/coherence/thinking. The item has been tested in multiple studies on its psychometric performance [ 23 , 24 ]. The wording of the item was: ‘Cognition, such as memory, understanding, concentration, thinking’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a frequently used item on cognitive problems in EQ-5D-5L format was included in the survey, informing on problems with memory/understanding/coherence/thinking. The item has been tested in multiple studies on its psychometric performance [ 23 , 24 ]. The wording of the item was: ‘Cognition, such as memory, understanding, concentration, thinking’.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of a cognition dimension to the EQ-5D has been studied more extensively than fatigue, and cognition has in many studies already been applied as an additional dimension of the EQ-5D [17]. However, while often suggested [16,32,33] and also tested for added value [23,24,28,34,[37][38][39][40], the cognition dimension is not an official EQ-5D dimension. Therefore, it is relevant to analyze the extent to which cognition is captured in a patient population with cognitive problems.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…Of the 28 articles that were included, 3 articles were studies that identified possible bolt-ons (category A "identification or development of possible suitable bolt-ons"), [23][24][25] 13 articles were psychometric performance studies (category B "psychometric performance studies"), 8,26-37 and 6 articles were valuation studies of EQ-5D 1 bolt-on (category C "health state valuation studies"). 19,20,[38][39][40][41][42] Furthermore, 3 articles were categorized as both categories A and B, [43][44][45] and 3 articles as both categories A and C. 13,21,38 Study populations consisted of a healthy population (n = 17 articles: general public, 13,[19][20][21]24,25,27,30,36,38,[40][41][42][43] random households, 44,45 faculty members 39 ) and patients (n = 11 articles: individuals with a chronic condition, 23 visitors of an outpatient eye clinic, 26 cognitive impaired elderly patients, 18 patients with diabetes, 28 general injury patients, 29,31,35 patients listed for cataract surgery, 32,34 stroke patients, …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the included studies were cross-sectional survey studies (N = 23), 13,[19][20][21][23][24][25][26][27][28][29][30][31]33,[36][37][38][39][40][41][42]44,45 of which 1 study also performed qualitative analysis. 21 In addition, there were 4 longitudinal survey studies 18,32,34,35 and 1 case study. 43 Furthermore, approximately half of the studies analyzed the 5-level version of the EQ-5D (N = 16).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation